PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN: GOOD CORPORATE GOVERNANCE VARIABEL MODERATING - Latupono, Siti Sapia; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to gain empirical evidences to the examination of the influenceof corporate social responsibility (CSR) to the firm value, the examination of the influence ofgood corporate governance to the firm values and the examination of the influence of corporatesocial responsibility which is moderated by good corporate governance to the firm value. Thesample collection technique has been done by using purposive sampling method. The dataanalysis techniques are multiple regression analysis and hypothesis test which is done by usingSPSS 20 version. Based on the results of the hypothesis test, it shows that corporate socialresponsibility has influence on the firm value and good corporate governance which is proxy bymanagerial ownership can influence the correlation between corporate social responsibility andfirm value.Keywords: Firm Value, Good Corporate Governance, and Corporate Social Responsibility.